SHOWING CULTURAL CONTEXT AND REVEALING CULTURAL MOTIVATION: “OBSERVATION” AND “PARTICIPATION” IN FOLK CULTURE DOCUMENTARIES - Peng Zhuang; Hani Salwah Yaakup; Siti Aishah binti Hj Mohammad Razi; Chin Mooi San (Fonseca, Journal of Communication, 2024)
“Observation” and “participation” are the two most important creation modes in the history of documentaries. Both represent different documentary ethics and views of the reality. This paper takes folk culture documentary as an example. It combines folk culture documentary with specific folk culture cases. It analyzes the ways of “observation” and “participation” in folk culture documentary production by showing cultural context, explaining human behavior, and revealing cultural motivation.